Fortifying angiogenic efficacy of conditioned media using phototoxic‐free blue light for wound healing - Sung‐Won Kim; Gwang‐Bum Im; Yeong Hwan Kim; Suk Ho Bhang (Wiley, 2023)
Abstract We used a blue organic light‐emitting diode (bOLED) to increase the paracrine factors secreted from human adipose‐derived stem cells (hADSCs) for producing conditioned medium (CM). Our results showed that while the bOLED irradiation promotes a mild‐dose reactive oxygen generation that enhances the angiogenic paracrine secretion of hADSCs, it does not induce phototoxicity. The bOLED enhances paracrine factors via a cell‐signaling mechanism involving hypoxia‐inducible factor 1 alpha. This study demonstrated that the CM resulting from bOLED treatment shows improved therapeutic effects on mouse wound‐healing models. This method contributes to overcoming the barriers to stem‐cell therapies, including the toxicity and low yields from other methods such as nanoparticles, synthetic polymers, and even cell‐derived vesicles.